Application of three-dimensional (3D) hand–eye calibration of industrial robot in laser cladding repair for drilling bit - J. Wang; Z. Mo; J. Wang; W. Pan (Mechanical Sciences)
In this paper, an entire process of laser cladding repair for damaged polycrystalline diamond compact (PDC) bits of high value based on a dual-robot system is proposed. First, the KUKA-KR20 industrial robot, along with a structural light three-dimensional (3D) scanner, is used to inspect the damaged bit, with point cloud data exported, and then the data are converted to the stereolithography (STL) file format in Geometric Studio, with the damaged region of the bit obtained after comparison with the standard model. Second, the KUKA-KR60 industrial robot holding a laser head is driven to realize cladding. In order to apply the information captured by the camera of the scanner to the laser cladding robot, a novel calibration, i.e., the three-point method for the dual-robot system, is proposed to transform the damaged region of the bit in the camera coordinate system to that in the cladding robot coordinate system, and then an upper computer program is developed to plan the cladding path for the laser head and to send the path to the KUKA-KR60 robot to complete cladding repair. Finally, a real experiment is carried out, which verifies that the dual-robot system has good flexibility and can be widely applied to different types of part repair with different types of blocky-surface damage.